Profil Kemampuan Komunikasi Matematika dengan Pembelajaran Joyful Learning Berbasis Konteks Budaya Melayu - Della Amrina Yusra (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2018)
The research underlying this paper is descriptive qualitative research conducted through three stages, the pre-field stage, the stage of field-work, and the data analysis stage. The subjects in this study were six students of grade seven Islamic Junior High School or Madrasah Tsanawiyah Yaspi Labuhan Medan with two subjects capable of good mathematical communication, two subjects with sufficient communication skills, and two subjects with less communication skills. Subject selected through purposive sampling. Based on the research, were obtained: first, there is a positive change in the ability of students to communicate mathematics after being given joyful learning based on the context of Malay culture; second, the process of student answers shows that subjects are better able to communicate mathematical questions after being given joyful learning based on Malay cultural context. Furthermore, this research recommended that teachers can use joyful learning based on cultural contexts by presenting problems related to local culture as an alternativelearning.